Transfusion associated graft versus host disease in an immunocompetent patient. Issue 7 (July 1992) - O'Connor, N T; Mackintosh, P
Abstract : Transfusion associated graft versus host disease is a rare disorder usually confined to patients who are immunosuppressed. A case is described in a 77 year old woman who was presumed immunocompetent. She was transfused with one unit of blood from an individual who was homozygous for the same HLA haplotype as her. The diagnosis of transfusion associated graft versus host disease should be suspected in a patient who develops aplastic anaemia within 30 days of a transfusion of blood products. It is suggested that blood donations from first degree relatives should not be permitted, unless the donation is irradiated to prevent lymphocyte proliferation.